Pengaruh Kombinasi Aplikasi Jamur Paecilomyces fumosoroseus, Lem Perangkap, dan Insektisida Imidakloprid terhadap Empoasca sp. - Fani Fauziah; Odih Sucherman (Jurusan Agroteknologi, 2017)
In order to obtain an effective and efficient control method in integrated pest management, a research to know the effectiveness of combination treatments on Empoasca sp. on tea plant had been conducted. The trial was carried out at Gambung Experimental Station (1,250 masl) and designed in Randomized Complete Block design (RCB), with 8 treatments and 3 replications. The treatment tested comprised with A. Paecilomyces fumosoroseus (Pfr); B. sticky trap (ST); C. imidacloprid (I); D. Pfr + ST; E. Pfr + I; F. ST + I; G. Pfr + ST + I; and H. control. Pfr multiplied in rice medium 2.5 kg ha-1 and imidacloprid 0.125 L ha-1 were sprayed, while sticky trap was set in the middle of 5 m x 5 m plot. The parameters observed were attack intensity of Empoasca sp., population of Empoasca sp, and tea shoot production. The results showed that after 3 times application of all treatments revealed a decrease in the attack intensity of Empoasca sp. After the fourth application, combination treatment of sticky trap (ST) + imidacloprid (I) consistently showed higher efficacy than other treatments. In the sixth observation, the average of Empoasca sp. attack intensity of combination treatment (ST + I) was 15.95% with an average population of 0.67 Empoasca sp. per plot. In the meantime, tea shoot production was 33.64% higher compared with control.